IMPLEMENTATION OF PROJECT BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING ACTIVITIES IN MECHANICAL ENGINEERING - Hilman, Antoni; Syahri, Budi; Refdinal, Refdinal; Rifelino, Rifelino (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2022)
The learning process in the classroom is the main key to the success of education, so the learning model applied by the teacher is important. This study aims to increase student learning activities in NC/CNC and CAM Machining Engineering subjects through the application of project based learning learning models, this is because the learning model applied by teachers has not varied which has an impact on declining student learning activities. This study uses the method of classroom action research (classroom action research). The subjects of this study were students of class XI TM 2, totaling 20 people. This research was conducted in May-June 2022. The instrument of this research used student learning activity observation sheets, with the acquisition of student learning activity results set at least 80% with good categories. The results of the first cycle of observations showed an average student learning activity of 69.94 % and in cycle 2 the average student learning activity is 81.14%. The increase in learning activities in cycle 1 and cycle 2 was 11.19%. The indicator of research success has been achieved in cycle 2 as evidenced by the acquisition of student learning activity results of 81.14%. The conclusion of this study is that the application of the project based learning model can improve student learning activities. The implication of this research is that it has an impact on learning NC/CNC and CAM Machining Techniques, which before the implementation of student learning activities were still low, after being implemented it was proven to increase student learning activities.